2023
DOI: 10.1097/aog.0000000000005130
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid and Fulfillment of Postpartum Permanent Contraception Requests

Abstract: Analysis of a multisite cohort reveals that efforts are needed to ensure that patients with Medicaid insurance who desire permanent contraception receive timely and equitable care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…However, the primary analysis from this cohort study revealed that cesarean delivery was the factor most strongly associated with fulfillment of postpartum permanent contraception. 12 Thus, the racial and ethnic differences in delivery type may interact with hospital-level barriers to permanent contraception among individuals who delivery vaginally, potentially Our findings thus reinforce the limitations of how race and ethnicity are often used in the scientific literature. When modeling associations between race, as a proxy for racism, and health outcomes, we often account for biological covariates such as age and parity.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…However, the primary analysis from this cohort study revealed that cesarean delivery was the factor most strongly associated with fulfillment of postpartum permanent contraception. 12 Thus, the racial and ethnic differences in delivery type may interact with hospital-level barriers to permanent contraception among individuals who delivery vaginally, potentially Our findings thus reinforce the limitations of how race and ethnicity are often used in the scientific literature. When modeling associations between race, as a proxy for racism, and health outcomes, we often account for biological covariates such as age and parity.…”
Section: Discussionsupporting
confidence: 52%
“…Multiple studies suggest that people with Medicaid insurance are less likely to have their desired postpartum permanent contraception procedure fulfilled. [6][7][8][9][10][11][12] As a result of structural racism and discrimination, Black and Hispanic people are more likely to have Medicaid insurance and therefore are more likely to face this policy as a barrier. 13 A study using longitudinal National Survey of Family Growth data from 2006 to 2010 reported that privately insured Black and Hispanic people were more likely to undergo permanent contraception compared with privately insured White people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are corrections to Arora et al 1 in the May 2023 issue. As the authors conducted secondary analyses of the data set, they discovered that 10 patients were miscoded in fulfillment of permanent contraception by 365 days (but were correctly classified at their endpoints by hospital discharge and 42 days postpartum).…”
mentioning
confidence: 99%
“…5 in the April 2023 issue is incorrect. 1 The correct title is, "Improving Access to Intrauterine Devices and Contraceptive Implants." In addition, the title in the citation at the end of the article on page 872 contains the incorrect title.…”
mentioning
confidence: 99%